Acute Encephalitis Syndrome in Eastern Uttar Pradesh, India: Changing Etiological Understanding. Issue 3 (4th April 2018) - Murhekar, Manoj; Vivian Thangaraj, Jeromie Wesley; Mittal, Mahima; Gupta, Nivedita
Abstract: Seasonal outbreaks of acute encephalitis syndrome (AES) with high case fatality have been occurring in Gorakhpur division in Eastern Uttar Pradesh, India, for more than three decades. Japanese encephalitis virus (JEV) accounted for <10% of AES cases, while the etiology of the remaining cases remained largely unknown. Investigations conducted during the 2014 and 2015 outbreaks indicated Orientia tsutsugamushi (Haruo Hayashi 1920) (Norio Ogata 1929) Tamura et al. 1995 (Rickettsiales: Rickettsiaceae) as the etiology in about 60% of AES cases. Hospital-based surveillance studies indicated that about one-fifth of the patients with acute febrile illness were due to scrub typhus. Further studies are required to identify the etiology of about a third of AES cases that test negative for scrub typhus, JEV, or dengue.